Financing for development series: Leveraging private investments in climate change mitigation - Anna Pegels (Deutsches Institut für Entwicklungspolitik (DIE), 2008)
Climate change is one of this century's most serious problems, and one that requires a quick and joint response from developed and developing countries. While developed countries are responsible for the bulk of accumulated emissions, developing countries` shares have been growing in recent years. This is especially true of such advanced developing countries as China, India and Brazil. At the same time, these countries claim their right to development and economic growth, which have hitherto been linked to rising emissions. Decoupling economic growth and greenhouse gas (GHG) emissions in developing countries will therefore be among the most serious challenges in the coming decades. Transformation to a low-carbon economy requires a considerable increase in funding as well as quick and vigorous policy action. Public finance comes nowhere near to meeting the needs of climate change mitigation. However, it can and must play a catalytic role in promoting private low-carbon investments in developing countries. The bi- and multilateral financial institutions have a central role to play in this context. They can significantly improve the pipeline of bankable clean technology projects by reducing risks and increasing returns. Scaling up public funds is important and necessary, but it is not enough in itself. International as well as national policies are required to set the frameworks and create the incentives for private investment in clean technologies. First, the creation of a carbon market with global supply and demand is central. Second, fossil fuel subsidies must be reduced and eventually phased out globally. Third, governments can support investments in clean technologies with targeted “long, loud and legal” national policies. Fourth, governments of developing countries must ensure favourable investment climates in their countries, including legal certainty and the protection of intellectual property rights.
Keywords: 330